2019
DOI: 10.5005/jp-journals-10015-1686
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Epidermal Growth Factor Receptor among Metastatic and Nonmetastatic Oral Squamous Cell Carcinomas

Abstract: Aim: To evaluate and correlate the epidermal growth factor receptor (EGFR) expression in oral squamous cell carcinomas (OSCC) patients with metastasis and without metastasis. Materials and methods:The study comprised of 40 samples, 20 cases of metastatic and 20 nonmetastatic OSCC. All the cases were immunostained for EGFR antibody. Epidermal growth factor receptor stained sections were evaluated for staining intensity and distribution. The differences between the groups were statistically analyzed using Chi-sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In contrast to Singla et al, 30 who observed a statistically significant relation between cases of leukoplakia, OSCC and control cases, and EGFR expression. Another study by Indrapriyadharshini et al 47 observed a statistically significant difference in EGFR expression between metastatic and nonmetastatic OSCC groups, with higher expression in the metastatic group.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to Singla et al, 30 who observed a statistically significant relation between cases of leukoplakia, OSCC and control cases, and EGFR expression. Another study by Indrapriyadharshini et al 47 observed a statistically significant difference in EGFR expression between metastatic and nonmetastatic OSCC groups, with higher expression in the metastatic group.…”
Section: Discussionmentioning
confidence: 91%